Arsenic Binding to Proteins - Shen, Shengwen; Li, Xing-Fang; Cullen, William R; Weinfeld, Michael; Le, X. Chris (Chemical reviews, 2013)
An overview of how arsenic binds to proteins is presented from an analytical and biochemical perspective. The binding affinity, kinetics and speciation of arsenic binding are also investigated.